Diseño y construcción de un equipo para medida de transporte eléctrico en nanosistemas - Yactayo, Gilberto (2023)
In this work we design and build a device to measure electrical transport using the Van Der Pauw technique for studies of nanosystems, such as copper and graphene thin films. One way to characterize these very fashionable materials is to measure their properties. electrical, which are a fingerprint of each material called electrical conductivity. Here we invent a switching system that allows alternating the measurements of the current and voltage that passes through the samples, this technique known as Van der Paw requires an arrangement of random contacts for data collection, allowing the measurement of the conductivity of the material under study to be obtained. for this work thin films of copper, graphene deposited on SiO2 at different temperatures. It has been found that the resistivity behavior of the measured Cu film agrees with the theoretical and experimental values of resistivity with increasing temperature.